Adhesion of enteropathogenic Escherichia coli to human intestinal enterocytes and cultured human intestinal mucosa. - Knutton, S (1987)
The adhesion of classic enteropathogenic Escherichia coli (EPEC) strains of human origin to isolated human small intestinal enterocytes and cultured small intestinal mucosa was investigated. An adhesion assay with isolated human enterocytes prepared from duodenal biopsy samples was developed and tested with EPEC strains known to cause diarrhea in healthy adult volunteers. In the assay a mean of 53 and 55% of enterocytes had brush border-adherent E. coli E2348 (O127;H6) and E851 (O142:H6), respectively, whereas the value for a nonpathogenic control strain and a plasmid-cured derivative of strain E2348 was 0%. A collection of 17 EPEC strains was also tested for the ability to colonize cultured human duodenal mucosa. Extensive colonization occurred with 13 strains, including serogroups O55, O86, O111, O114, O119, O127, O128, and O142; and in each case electron microscopic examination of colonized mucosa revealed the characteristic histopathological lesion reported by others in natural and experimental EPEC infections. EPEC strains were seen to adhere intimately to the enterocyte surface, causing localized destruction of microvilli. The plasmid-cured derivative of strain E2348, which colonized cultured mucosa much less efficiently than the parent strain, nevertheless produced an identical lesion, indicating that plasmid-encoded factors are not essential for adhesion and the brush border-damaging property of EPEC.